Silver triflate catalyzed cyclopropyl carbinol rearrangement for benzo[b]oxepine and 2H-chromene synthesis - Chan, Philip Wai Hong (2015)
An efficient AgOTf-catalyzed (TfO = trifluoromethanesulfonate) cyclopropyl carbinol rearrangement for the synthesis of benzo[b]oxepines and 2H-chromenes is reported by starting from 2-[cyclopropyl(hydroxy)methyl]phenols. The reactions proved to be general in scope and furnished a range of the corresponding functionalized oxygen heterocycles. The formation of the benzo-fused six-membered adduct is proposed to result from the ring-contraction of the benzo[b]oxepine derivative. Control of the product selectivity is achievable by fine-tuning the reaction time. The catalytic synergy between the silver(I) cation and the triflate anion was essential for optimal product yields.